Society Information. (Papers of the Bibliographical Society of America, 2024)
The Bibliographical Society of America is seeking nominations for new council members who will be elected at their Annual Meeting in January 2025. They are particularly interested in nominees who represent the racial and ethnic diversity of bibliographical communities in the United States. Council members are responsible for setting strategic priorities, approving the annual budget, and fundraising. They are also invited to join committees and working groups based on their interests and experience. The society encourages officers and council members to make a financial contribution to the annual fund, but there is no minimum requirement. Membership dues start at $25 for individuals 35 and younger, and $80 for individuals 36 and older. The society also calls for submissions to their open-access digital repository, BibSite, and their journal, the Papers of the Bibliographical Society of America.